Patients’ perspectives of epilepsy care by specialists and generalists: qualitative evidence synthesis - Charlotte L Cotterill; Andrew Booth; Jon M Dickson; Daniel Hind (BJGP Open)
Background: In the UK, epilepsy care involves both specialists (for example, neurologists) and generalists (for example, GPs). Policymakers typically consider that epilepsy care should be integrated and involve both specialists and generalists. However, few understand exactly how patients view and compare specialist and generalist care. Aim: To explore patient perspectives of specialist care and generalist care for epilepsy in a qualitative evidence synthesis. Design & setting: A systematic review of patient perspectives of epilepsy care. A qualitative evidence synthesis was conducted using an identified framework. Method: Systematic searches in five databases retrieved 17 eligible studies. Data were extracted and synthesised using framework analysis informed by the ‘United Model of Generalism’. Results: The following three themes were developed: ‘Epilepsy care can be burdensome’ (for example, through care fragmentation); ‘Patients' experiences of care is that care is not always accessible’ (for example, lack of a continuum between standardised and interpretive care); and ‘How care could change for people with epilepsy’ (for example, clinicians currently have insufficient time to deviate from protocol-driven care to address psychosocial needs). People with epilepsy frequently observe that generalists lack expertise in epilepsy management. Conclusion: This synthesis of patient experiences indicates recommendations should focus on improving communication and integration between specialists and generalists for epilepsy care. Patient experiences indicate specialist care risks being burdensome and generalist knowledge insufficient, requiring enhanced primary care clinician skills and improved awareness of patient psychosocial needs. The findings argue in favour of healthcare policies, materials, and tools to continually support patient perspectives in developing epilepsy services.